Empowerment through advertisements: the social responsible role of depicting images of special needs for normalcy - Mokhtar, Aida (2019)
Media messages are capable of fashioning our perception of reality through the empowerment of distinctive images of people special needs. Without the existence of special needs representation in advertising, there could be the absence of the inclusion of people with special needs in mainstream society. The act of normalising distinctions through dignified portrayals of special needs people that are diverse could be an additional function of advertising in addition to bringing people together at the marketplace. An organisation involved in normalising people with special needs as part of society is a noble act that should be encouraged similarly to upholding the visibility of a brand. Several objectives could be met through advertising from inculcating positive attitudes to special needs people, encouraging values in people, normalising special needs people by mainstream society and promoting goodwill to the organisation. Without such visible depictions, people with special needs could encounter possible exclusion from society initiated from a negative attitude to them. Values such as compassion, and empathy could be communicated through these depictions and inculcated within the audience. These efforts could be part of the organisation’s initiative in being socially responsible. A socially responsible organisation could encourage goodwill from the public through the act of normalising distinctions in the form of special needs.